Sex estimation using discriminant function analysis of the maximum length of clavicle: An autopsy-based study in Central India - Singh, Anuradha; Baraw, Rajendra; Yadav, Jayanthi; Tomar, Anurag; Saxena, Aditya; Arora , Abhishek (Journal of Indian Academy of Forensic Medicine, 2021)
Identification is the determination of the individuality of a person based on certain physical characteristics. Clavicle is one of the bones which is less explored but has drawn considerable interest in this field, particularly in relation to sexual dimorphism. The purpose of this research was to evaluate the sexual dimorphism of clavicle, based on measurement of the maximum length of dry clavicles. The study was conducted in the mortuary of the Department of Forensic Medicine, Gandhi Medical College, on 100 cases (50 males; 50 females) in which post-mortem examination was done. Clavicle bone of deceased aged between25 to 60 years were collected during autopsy, dried and then examined for the study. Approval of the Institutional Ethics Committee was obtained prior to the commencement of the study. Maximum length of clavicle was found to be larger in males as compared to females in dry clavicle. By discriminant function analysis, sex can be estimated with an accuracy of about 75%. However, these values were found to be more accurate in males with accuracy of 80% for males and 70% for females. Determination of sex by means of maximum length of clavicle can be considered a reliable indicator in dried state of the bone and the accuracy rate was high for males than females.